Flaky composite lithium manganese iron phosphate material and preparation method thereof
By adding Mg, V and Nb elements into lithium manganese phosphate material and using high-energy ball milling and carbon cladding technology to form a sheet-like composite material, the problem of low energy density of lithium manganese phosphate material is solved and the further development is achieved High energy density and electrochemical properties.
Patent Information
- Application Number
- CN202411360498.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The existing lithium iron phosphate materials have low energy density, and the compaction density and gram capacity are difficult to be better than lithium iron phosphate materials at the same time.
Using a sheet-like composite lithium manganese iron phosphate material, the material with excellent electrochemical properties is formed by incorporating Mg elements, V elements and Nb elements into the lithium manganese iron phosphate structure, and combining high-energy ball mill activation and carbon cladding layer. .
The energy density, discharge specific capacity, rate performance and cycle stability of sheet-shaped composite lithium manganese iron phosphate materials have been significantly improved, and the problem of insufficient energy density of traditional materials has been solved.
Smart Images

Figure CN119419229A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a sheet-like composite lithium manganese iron phosphate material and a preparation method thereof. Background Art
[0002] As an "upgraded version" of lithium iron phosphate cathode materials, lithium manganese iron phosphate inherits the advantages of LFP such as low cost, high thermal stability, and high safety, and makes up for its disadvantages such as low energy density and poor low-temperature performance. However, LMFP also has problems such as poor conductivity, rate performance, and cycle performance. At present, coating, nano-sizing, and morphology control shorten the migration path of lithium ions by changing external features and constructing a fast conductive network; ion doping changes the internal crystal structure, causing defects in the original lattice, making Li + The expansion of diffusion channels and the increase of material carrier density can improve the electrochemical performance of LMFP to a certain extent.
[0003] Regarding the preparation method of lithium iron manganese phosphate in the prior art, such as the Chinese patent application with patent application number 202210309750.1, a single-core multi-shell lithium iron manganese phosphate positive electrode material is provided to prepare carbon-coated lithium iron manganese phosphate particles of different particle sizes; using the carbon-coated lithium iron phosphate particles as the inner core, and sequentially preparing the lithium iron manganese phosphate coating layer on the outer surface of the inner core in the order of the particle size of the carbon-coated lithium iron manganese phosphate particles from small to large, to form multiple lithium iron manganese phosphate coating layers, and obtain a single-core multi-shell lithium iron manganese phosphate composite material, but there are multiple layers of coating, the process flow is complicated, and it is not conducive to large-scale production. For example, a Chinese patent application with patent application number 202111667352.9 provides a high-compacted phosphate-type positive electrode material, including a dual-morphological phosphate-type positive electrode material, and the dual-morphological phosphate-type positive electrode material includes a spherical phosphate-type positive electrode material and a flaky phosphate-type positive electrode material. By compounding the spherical phosphate-type positive electrode material and the flaky phosphate-type positive electrode material, the compaction density and capacity ratio of the positive electrode material are taken into account at the same time, thereby synergistically improving the energy density of the positive electrode material. However, the simple mixing of the dual-morphological phosphate-type positive electrode material may have poor uniformity and the local particles are not in close contact, resulting in the problem that the material performance cannot be fully exerted.
[0004] Although the size of common lithium iron manganese phosphate particles (between 100nm and 200nm) is smaller than the 300nm to 400nm of lithium iron, small-particle lithium iron manganese phosphate will bring higher capacity and better rate, but it will also cause problems such as low compaction density and processing difficulty of lithium iron manganese phosphate materials.
[0005] At present, the energy density of lithium iron phosphate materials is still lower than that of mature lithium iron phosphate materials, mainly because it is difficult for the compaction density and gram capacity of lithium iron phosphate materials to be better than lithium iron phosphate materials at the same time. For lithium iron phosphate, the scheme of improving the material's conductivity and lithium ion diffusion rate often reduces the compaction density of lithium iron phosphate materials, making it difficult to effectively improve the energy density of lithium iron phosphate materials. Summary of the invention
[0006] The main purpose of the present invention is to provide a sheet-like composite lithium iron manganese phosphate material and a preparation method thereof, so as to solve the problem of low energy density of lithium iron manganese phosphate materials in the prior art.
[0007] In order to achieve the above object, according to one aspect of the present invention, a sheet-like composite lithium iron manganese phosphate material is provided, the sheet-like composite lithium iron manganese phosphate material comprising a composite lithium iron manganese phosphate core and a carbon coating layer coated on the surface of the composite lithium iron manganese phosphate core, wherein the chemical formula of the composite lithium iron manganese phosphate core is LiFe x Mn y A z PO4, wherein 0.2≤x≤0.4, 0.57≤y≤0.78, x+y+z=1; A represents Mg element, V element and Nb element; the sheet diameter of the flaky composite lithium manganese iron phosphate material is 0.5-2 μm, and the tap density of the flaky composite lithium manganese iron phosphate material is 0.9 g / cc-1.2 g / cc.
[0008] Furthermore, the lattice parameters of the above-mentioned sheet-shaped composite lithium manganese iron phosphate material are:
[0009] The flaky structure of the flaky composite lithium iron manganese phosphate material of the present application helps to reduce the size of the flaky composite lithium iron manganese phosphate material in the b-axis direction and expand its size in the a-axis direction and c-axis direction, thereby greatly shortening the diffusion path of lithium ions and having better lithium ion diffusion kinetics, while taking into account the compaction density and capacity ratio of the flaky composite lithium iron manganese phosphate material, thereby synergistically improving the energy density of the flaky composite lithium iron manganese phosphate material.
[0010] Furthermore, the mass content of the Mg element is 2000ppm to 3000ppm, the mass content of the V element is 100ppm to 1000ppm, and the mass content of the Nb element is 1000ppm to 2000ppm.
[0011] By controlling the mass content range of the doping elements Mg, Nb and V and the mass content ratio of the three doping elements within the above ranges, it is helpful to improve the synergistic effect of the three doping elements, thereby synergistically improving the energy density of the flaky composite lithium manganese iron phosphate material.
[0012] Furthermore, the thickness of the above-mentioned sheet-like composite lithium manganese iron phosphate material is 0.2 μm to 0.5 μm; and / or the mass of the carbon coating layer is 1.5 to 2% of the mass of the sheet-like composite lithium manganese iron phosphate material.
[0013] By controlling the thickness of the sheet-like composite lithium manganese iron phosphate material within the above range, it is more helpful to improve the size matching between the sheet structures of the sheet-like composite lithium manganese iron phosphate material, thereby helping to improve the packing density of the sheet-like composite lithium manganese iron phosphate material, reduce the insertion / extraction path of lithium ions, and thus be beneficial to improve the electrochemical properties of the sheet-like composite lithium manganese iron phosphate material, especially the rate performance. The preferred carbon coating layer with the above content helps to give full play to the activity of manganese ions, thereby improving the electrical properties of the sheet-like composite lithium manganese iron phosphate material.
[0014] According to another aspect of the present invention, there is provided a method for preparing the aforementioned flaky composite lithium iron manganese phosphate material, the preparation method comprising: step S1, mixing raw materials including a lithium source, an iron source, a manganese source, a phosphorus source, a carbon source, and a doping source and grinding them to obtain a ground slurry; step S2, spraying the ground slurry to obtain a yellow material, and sintering the yellow material in a protective atmosphere to obtain a black material; step S3, high-energy ball milling activation of the raw materials including the black material, a molten salt medium and a conductive additive to obtain an activated mixture; step S4, sequentially melting, filtering, washing and drying the activated mixture to obtain a flaky composite lithium iron manganese phosphate material; wherein the doping source comprises a Mg source, a V source and a Nb source.
[0015] On the one hand, the present application activates the molten salt medium through high-energy ball milling, so that a liquid phase appears during the synthesis process of the composite manganese iron phosphate lithium material, so that the reaction raw materials have a certain solubility therein, so that the reaction is converted from a solid-solid reaction to a solid-liquid reaction, thereby greatly accelerating the diffusion rate of the reactant ions, avoiding the problem that the traditional high-temperature solid phase is prone to local unevenness and high energy consumption, and also avoiding the limitations of the hydrothermal method. On the other hand, the nanoparticle raw material undergoes a high shear force in the mechanical melting process in the liquid molten salt, so that the microstructure of the nanoparticles is reshaped into a flaky form. Compared with the morphology of the original spherical particle manganese iron phosphate lithium, the stacking density of the flaky composite manganese iron phosphate lithium material is improved, thereby improving the energy density of the phosphate-type positive electrode material. At the same time, the present application introduces Mg elements, V elements and Nb elements into the structure of lithium manganese iron phosphate, combining the advantages of each doped metal ion, and can improve the crystal structure, conductivity and cycle performance of the material.
[0016] Further, in the above step S1, the carbon source includes glucose, preferably the carbon source is a mixture of glucose and polyvinyl alcohol, preferably the mass ratio of glucose to polyvinyl alcohol is (7-9): (3-1), and preferably the polyvinyl alcohol is 88 series polyvinyl alcohol; and / or the Mg source is selected from any one or more of magnesium oxide, magnesium carbonate, magnesium acetate, magnesium lactate, magnesium dihydride and magnesium hydroxide; and / or the V source is selected from any one or more of vanadium pentoxide, ammonium metavanadate, vanadium carbide and vanadium oxalate; and / or the Nb source is niobium pentoxide and / or niobium oxalate; and / or the lithium source is selected from any one or more of lithium carbonate, lithium hydroxide, lithium acetate and lithium oxalate; and / or the iron source is selected from any one or more of ferric phosphate, ferric oxide, ferric oxide, ferric hydroxide, ferric lactate and ferrous oxalate; and / or the manganese source is selected from any one or more of manganese tetraoxide, manganese carbonate, manganese dioxide and manganese trioxide; and / or the phosphorus source is selected from any one or more of phosphoric acid, ferric phosphate, ammonium phosphate, diammonium hydrogen phosphate and ammonium dihydrogen phosphate.
[0017] The preferred carbon source is a mixture of glucose and polyvinyl alcohol and the mass ratio of the two is controlled within the above range, which helps to utilize the different carbonization temperatures of the two to make the doping in the sheet-like composite lithium iron manganese phosphate material more uniform. The preferred Mg source, V source and Nb source are of the above types, which make it easier to dissolve in the liquid molten salt medium, so that it can be more uniformly doped inside the lithium iron manganese phosphate crystal structure to optimize the lattice of the lithium iron manganese phosphate. The preferred iron source, phosphorus source and manganese source help to improve the synergistic effect with other metal sources.
[0018] Furthermore, in the above step S1, the raw material also includes a solvent, preferably the solvent is selected from any one or more of water, ethanol, methanol and propylene glycol, and / or the solid content of the slurry after grinding is 30% to 50%, and / or the sand grinding particle size D50 during the grinding process is controlled to be 0.3μm to 0.4μm.
[0019] The solvent is preferably one or more of the above ranges, which is conducive to improving the uniform dispersion of each raw material during the grinding process, avoiding the aggregation of the raw materials, and ensuring the uniformity of the grinding process. The solid content of the slurry after grinding is preferably within the above range, which helps to increase the diffusion rate of lithium ions, thereby improving the energy density and performance of the composite manganese iron phosphate lithium material. By controlling the sand grinding particle size during the grinding process within the above range, it helps to increase the diffusion coefficient of lithium ions, so that the compaction density of the composite manganese iron phosphate lithium material can be increased while ensuring high capacity and high rate, thereby improving its charge and discharge performance and cycle stability.
[0020] Furthermore, in the above step S2, the protective atmosphere is a nitrogen atmosphere; and / or the sintering temperature is 700° C. to 750° C., and the sintering time is 6 h to 10 h.
[0021] The above preferred conditions are conducive to improving the efficiency and effect of sintering, thereby improving the high crystallinity and stability of the structural crystal form of the sheet-like composite lithium manganese iron phosphate material.
[0022] Furthermore, in the above step S3, the rotation speed of the high-energy ball mill is 400rpm~800rpm; the time of the high-energy ball milling is 3h~8h; the mass ratio of the black material to the molten salt medium is 1:(3~5), and / or the melting temperature of the molten salt medium is lower than 600°C, preferably the melting temperature of the molten salt medium is 170°C~600°C, preferably the molten salt medium is selected from at least two of LiCl, Li2SO4, LiClO4, LiBO2, LiAc, LiNO3, LiOH, Li2CO3 and LiBr; and / or the conductive additive is a flaky conductive agent, preferably the flaky conductive agent is selected from any one or more of flaky graphite, graphene and flaky MXene.
[0023] By controlling the rotation speed and time of high-energy ball milling within the above range, it is helpful to improve the efficiency and effect of high-energy ball milling. The melting temperature of the molten salt medium is preferably within the above range, which helps to provide a liquid phase medium for high-energy ball milling, thereby promoting the transformation of the original nanoparticles into flaky particles, and solving the current technical problem of insufficient energy density caused by the inability to simultaneously increase the compaction density and gram capacity due to the small particle size of the lithium manganese iron phosphate material. It is preferred to control the mass ratio of the black material to the molten salt medium within the above range, which is beneficial to improve the dispersion effect of the black material in the liquid molten salt medium. The above types of preferred conductive additives help to improve the conductive properties of the flaky composite lithium manganese iron phosphate material.
[0024] Furthermore, in the above step S4, the temperature during the melting process is 400° C. to 600° C., and the insulation time is 5 h to 10 h.
[0025] By controlling the melting temperature and the holding time within the above ranges, the efficiency and effect of melting the activated mixture can be improved, thereby improving the electrochemical properties of the flaky composite lithium manganese iron phosphate material.
[0026] By applying the technical solution of the present invention, in the sheet-shaped composite lithium manganese iron phosphate material of the present application, by doping Mg, V and Nb elements into the lithium manganese iron phosphate structure, the advantages of each doped metal ion can be combined to improve the crystal structure, electrical conductivity and cycle performance of the sheet-shaped composite lithium manganese iron phosphate material. Specifically, due to Mg 2+ The ionic radius is smaller than that of Mn 2+ After doping, the MO bond length in the MO6 octahedron becomes shorter, and the Li-O bond length in the LiO6 octahedron becomes longer. The extension of the Li-O bond makes the Li + The diffusion channel of Li is wider. +It is easier to migrate, thereby increasing the carrier density of the sheet-like composite lithium manganese iron phosphate material, which is beneficial for the multi-component olivine structure cathode material to have better electrochemical performance. 5+ and Nb 5+ Ion defects are generated, and mixed valence states are favorable for Li + De-embedding inside the material. By changing the crystal structure inside the lithium manganese iron phosphate through ion doping, the original lithium manganese iron phosphate lattice has defects, making Li + The diffusion channel is expanded, and the carrier density of the flaky composite lithium iron manganese phosphate material is increased, which can improve the electrochemical performance of the flaky composite lithium iron manganese phosphate material to a certain extent. Therefore, by doping Mg, V and Nb elements, the lithium iron manganese phosphate nanoparticles are reconstructed into a flaky form through microstructure, and the sheet diameter of the flaky composite lithium iron manganese phosphate material is 0.5μm to 2μm, so that compared with the original morphology of lithium iron manganese phosphate, the powder packing density of the flaky composite lithium iron manganese phosphate material in this application is improved, thereby improving the energy density of the flaky composite lithium iron manganese phosphate material. In addition, the carbon coating layer helps to significantly improve the electrical properties of the flaky composite lithium iron manganese phosphate material, such as energy density, discharge specific capacity, rate performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0028] Figure 1 The phase diagram curve of LiOH-LiCl is shown;
[0029] Figure 2 The XRD pattern of the composite lithium iron manganese phosphate electrode material prepared in Example 1 is shown;
[0030] Figure 3 The SEM image of the composite lithium iron manganese phosphate electrode material prepared in Example 1 is shown;
[0031] Figure 4 The figure shows the SEM image of nano-lithium iron manganese phosphate material sold on the market. DETAILED DESCRIPTION
[0032] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0033] As analyzed in the background technology, the lithium manganese iron phosphate material in the prior art has the problem of low energy density. To solve this problem, the present invention provides a sheet-like composite lithium manganese iron phosphate material and a preparation method thereof.
[0034] In a typical embodiment of the present application, a sheet-like composite lithium iron manganese phosphate material is provided, wherein the sheet-like composite lithium iron manganese phosphate material comprises a composite lithium iron manganese phosphate core and a carbon coating layer coated on the surface of the composite lithium iron manganese phosphate core, wherein the chemical formula of the composite lithium iron manganese phosphate core is LiFe x Mn y A z PO4, wherein 0.2≤x≤0.4, 0.57≤y≤0.78, x+y+z=1; A represents Mg element, V element and Nb element; the sheet diameter of the flaky composite manganese iron phosphate lithium material is 0.5μm~2μm, and the tap density of the flaky composite manganese iron phosphate lithium material is 0.9g / cc~1.2g / cc.
[0035] In the sheet-shaped composite lithium manganese iron phosphate material of the present application, by doping Mg, V and Nb into the lithium manganese iron phosphate structure, the advantages of each doped metal ion can be combined to improve the crystal structure, electrical conductivity and cycle performance of the sheet-shaped composite lithium manganese iron phosphate material. 2+ The ionic radius is smaller than that of Mn 2+ After doping, the MO bond length in the MO6 octahedron becomes shorter, and the Li-O bond length in the LiO6 octahedron becomes longer. The extension of the Li-O bond makes the Li + The diffusion channel of Li is wider. + It is easier to migrate, thereby increasing the carrier density of the sheet-like composite lithium manganese iron phosphate material, which is beneficial for the multi-component olivine structure cathode material to have better electrochemical performance. 5+ and Nb 5+ Ion defects are generated, and mixed valence states are favorable for Li + De-embedding inside the material. By changing the crystal structure inside the lithium manganese iron phosphate through ion doping, the original lithium manganese iron phosphate lattice has defects, making Li + The diffusion channel is expanded, and the carrier density of the flaky composite lithium iron manganese phosphate material is increased, which can improve the electrochemical performance of the flaky composite lithium iron manganese phosphate material to a certain extent. Therefore, by doping Mg, V and Nb elements, the lithium iron manganese phosphate nanoparticles are reconstructed into a flaky form through microstructure, and the sheet diameter of the flaky composite lithium iron manganese phosphate material is 0.5μm to 2μm, so that compared with the original morphology of lithium iron manganese phosphate, the powder packing density of the flaky composite lithium iron manganese phosphate material in this application is improved, thereby improving the energy density of the flaky composite lithium iron manganese phosphate material. In addition, the carbon coating layer helps to significantly improve the electrical properties of the flaky composite lithium iron manganese phosphate material, such as energy density, discharge specific capacity, rate performance and cycle stability.
[0036] In one embodiment of the present application, the lattice parameters of the above-mentioned sheet-shaped composite lithium manganese iron phosphate material are:
[0037] Compared with traditional spherical particles of lithium manganese iron phosphate, the flaky structure of the flaky composite lithium manganese iron phosphate material of the present application helps to reduce the size of the flaky composite lithium manganese iron phosphate material in the b-axis direction and expand its size in the a-axis direction and c-axis direction, thereby greatly shortening the diffusion path of lithium ions and having better lithium ion diffusion kinetics, while taking into account the compaction density and capacity ratio of the flaky composite lithium manganese iron phosphate material, thereby synergistically improving the energy density of the flaky composite lithium manganese iron phosphate material.
[0038] In one embodiment of the present application, the mass content of the Mg element is 2000ppm to 3000ppm, the mass content of the V element is 100ppm to 1000ppm, and the mass content of the Nb element is 1000ppm to 2000ppm.
[0039] By controlling the mass content range of the doping elements Mg, Nb and V and the mass content ratio of the three doping elements within the above ranges, it is helpful to improve the synergistic effect of the three doping elements, thereby synergistically improving the energy density of the flaky composite lithium manganese iron phosphate material.
[0040] In one embodiment of the present application, the thickness of the above-mentioned flaky composite lithium manganese iron phosphate material is 0.2 μm to 0.5 μm; and / or the mass of the carbon coating layer is 1.5 to 2% of the mass of the flaky composite lithium manganese iron phosphate material.
[0041] By controlling the thickness of the sheet-like composite lithium manganese iron phosphate material within the above range, it is more helpful to improve the size matching between the sheet structures of the sheet-like composite lithium manganese iron phosphate material, thereby helping to improve the packing density of the sheet-like composite lithium manganese iron phosphate material, reduce the insertion / extraction path of lithium ions, and thus be beneficial to improve the electrochemical properties of the sheet-like composite lithium manganese iron phosphate material, especially the rate performance. The preferred carbon coating layer with the above content helps to give full play to the activity of manganese ions, thereby improving the electrical properties of the sheet-like composite lithium manganese iron phosphate material.
[0042] In another typical embodiment of the present application, a method for preparing a flaky composite lithium iron manganese phosphate material is provided, and the preparation method comprises: step S1, mixing raw materials including a lithium source, an iron source, a manganese source, a phosphorus source, a carbon source, and a doping source and grinding them to obtain a ground slurry; step S2, spraying the ground slurry to obtain a yellow material, and sintering the yellow material in a protective atmosphere to obtain a black material; step S3, high-energy ball milling activation of the raw materials including the black material, a molten salt medium and a conductive additive to obtain an activated mixture; step S4, melting, filtering, washing and drying the activated mixture in sequence to obtain a flaky composite lithium iron manganese phosphate material; wherein the doping source comprises a Mg source, a V source and a Nb source.
[0043] On the one hand, the present application activates the molten salt medium through high-energy ball milling, so that a liquid phase appears during the synthesis process of the composite manganese iron phosphate lithium material, so that the reaction raw materials have a certain solubility therein, so that the reaction is converted from a solid-solid reaction to a solid-liquid reaction, thereby greatly accelerating the diffusion rate of the reactant ions, avoiding the problem that the traditional high-temperature solid phase is prone to local unevenness and high energy consumption, and also avoiding the limitations of the hydrothermal method. On the other hand, the nanoparticle raw material undergoes a high shear force in the mechanical melting process in the liquid molten salt, so that the microstructure of the nanoparticles is reshaped into a flaky form. Compared with the morphology of the original spherical particle manganese iron phosphate lithium, the stacking density of the flaky composite manganese iron phosphate lithium material is improved, thereby improving the energy density of the phosphate-type positive electrode material. At the same time, the present application introduces Mg elements, V elements and Nb elements into the structure of lithium manganese iron phosphate, combining the advantages of each doped metal ion, and can improve the crystal structure, conductivity and cycle performance of the material.
[0044] In one embodiment of the present application, in the above step S1, the carbon source includes glucose, preferably the carbon source is a mixture of glucose and polyvinyl alcohol, preferably the mass ratio of glucose to polyvinyl alcohol is (7-9): (3-1), and preferably the polyvinyl alcohol is 88 series polyvinyl alcohol; and / or the Mg source is selected from any one or more of magnesium oxide, magnesium carbonate, magnesium acetate, magnesium lactate, magnesium dihydride and magnesium hydroxide; and / or the V source is selected from any one or more of vanadium pentoxide, ammonium metavanadate, vanadium carbide and vanadium oxalate; and / or the Nb source is selected from any one or more of niobium pentoxide and / or niobium oxalate; and / or the lithium source is selected from any one or more of lithium carbonate, lithium hydroxide, lithium acetate and lithium oxalate; and / or the iron source is selected from any one or more of ferric phosphate, ferric oxide, ferric oxide, ferric hydroxide, ferric lactate and ferrous oxalate; and / or the manganese source is selected from any one or more of manganese tetraoxide, manganese carbonate, manganese dioxide and manganese trioxide; and / or the phosphorus source is selected from any one or more of phosphoric acid, ferric phosphate, ammonium phosphate, diammonium hydrogen phosphate and ammonium dihydrogen phosphate.
[0045] The preferred carbon source is a mixture of glucose and polyvinyl alcohol and the mass ratio of the two is controlled within the above range, which helps to utilize the different carbonization temperatures of the two to make the doping in the sheet-like composite lithium iron manganese phosphate material more uniform. The preferred Mg source, V source and Nb source are of the above types, which make it easier to dissolve in the liquid molten salt medium, so that it can be more uniformly doped inside the lithium iron manganese phosphate crystal structure to optimize the lattice of the lithium iron manganese phosphate. The preferred iron source, phosphorus source and manganese source help to improve the synergistic effect with other metal sources.
[0046] In one embodiment of the present application, in the above step S1, the raw material also includes a solvent, preferably the solvent is selected from any one or more of water, ethanol, methanol and propylene glycol, and / or the solid content of the slurry after grinding is 30% to 50%, and / or the sand grinding particle size D50 during the grinding process is controlled to be 0.3μm to 0.4μm.
[0047] The solvent is preferably one or more of the above ranges, which is conducive to improving the uniform dispersion of each raw material during the grinding process, avoiding the aggregation of the raw materials, and ensuring the uniformity of the grinding process. The solid content of the slurry after grinding is preferably within the above range, which helps to increase the diffusion rate of lithium ions, thereby improving the energy density and performance of the composite manganese iron phosphate lithium material. By controlling the sand grinding particle size during the grinding process within the above range, it helps to increase the diffusion coefficient of lithium ions, so that the compaction density of the composite manganese iron phosphate lithium material can be increased while ensuring high capacity and high rate, thereby improving its charge and discharge performance and cycle stability.
[0048] In one embodiment of the present application, in the above step S2, the protective atmosphere is a nitrogen atmosphere; and / or the sintering temperature is 700° C. to 750° C., and the sintering time is 6 h to 10 h.
[0049] The above preferred conditions are conducive to improving the efficiency and effect of sintering, thereby improving the high crystallinity and stability of the structural crystal form of the sheet-like composite lithium manganese iron phosphate material.
[0050] In one embodiment of the present application, in the above step S3, the rotation speed of the high-energy ball mill is 400rpm~800rpm; the time of the high-energy ball milling is 3h~8h; the mass ratio of the black material to the molten salt medium is 1:(3~5), and / or the melting temperature of the molten salt medium is lower than 600°C, preferably the melting temperature of the molten salt medium is 170°C~600°C, preferably the molten salt medium is selected from at least two of LiCl, Li2SO4, LiClO4, LiBO2, LiAc, LiNO3, LiOH, Li2CO3 and LiBr; and / or the conductive additive is a flaky conductive agent, preferably the flaky conductive agent is selected from any one or more of flaky graphite, graphene and flaky MXene.
[0051] By controlling the rotation speed and time of high-energy ball milling within the above range, it is helpful to improve the efficiency and effect of high-energy ball milling. The melting temperature of the molten salt medium is preferably within the above range, which helps to provide a liquid phase medium for high-energy ball milling, thereby promoting the transformation of the original nanoparticles into flaky particles, and solving the current technical problem of insufficient energy density caused by the inability to simultaneously increase the compaction density and gram capacity due to the small particle size of the lithium manganese iron phosphate material. It is preferred to control the mass ratio of the black material to the molten salt medium within the above range, which is beneficial to improve the dispersion effect of the black material in the liquid molten salt medium. The above types of preferred conductive additives help to improve the conductive properties of the flaky composite lithium manganese iron phosphate material.
[0052] In one embodiment of the present application, in the above step S4, the temperature during the melting process is 400°C to 600°C, and the insulation time is 5h to 10h.
[0053] By controlling the melting temperature and the holding time within the above ranges, the efficiency and effect of melting the activated mixture can be improved, thereby improving the electrochemical properties of the flaky composite lithium manganese iron phosphate material.
[0054] The beneficial technical effects of the present application will be described below in combination with specific embodiments and comparative examples.
[0055] Example 1
[0056] FeC2O4, MnC2O4, LiH2PO4, and Li2CO3 were weighed in a molar ratio of 0.4:0.578:1:0.008, added into deionized water, and mixed evenly to obtain slurry (I), wherein the solid content of slurry (I) was 40%; glucose and polyvinyl alcohol 17-88 were weighed in a mass ratio of 8:1 as carbon sources, and the mass of the carbon source accounted for 12% of the total mass of the raw materials; 0.018 mol of Mg element (added in the form of MgO) was added according to the theoretical product, and 0.002 mol of Nb element (added in the form of Nb2O5) and 0.002 mol of V element (added in the form of V2O5), all the above raw materials are mixed and ground with a sand mill, and the D50 of the slurry is ground to 350nm, and the solid content of the slurry after grinding is 40%; then the ground slurry is introduced into a spray dryer for spraying and drying to obtain a yellow material, and the dried yellow material is transferred to a box furnace, sintered at 700℃ for 8h in a nitrogen atmosphere, and naturally cooled to room temperature to obtain a black material.
[0057] Take 50g of the above black material, add 200g of molten salt medium (LiCl:LiOH=37:63mol%) and 0.5g of conductive graphite for high-energy ball milling activation, the speed of high-energy ball milling is 600rpm, and the time of high-energy ball milling is 5h to obtain an activated mixture. The activated mixture is transferred to a box furnace and heated to 500℃ for secondary growth under molten salt conditions, and then naturally cooled to a temperature below 50℃. The powder is stirred in deionized water for 0.5h to remove the molten salt medium, and then placed in a vacuum drying oven for drying to obtain a sheet-like composite manganese iron phosphate lithium material with a thickness of 0.3μm and a sheet diameter of 1μm. The chemical formula of the composite manganese iron phosphate lithium core is LiFe 0.4 Mn 0.578 Mg 0.018 Nb 0.002 V 0.002 PO4, wherein the mass of the carbon coating layer is 1.8% of the mass of the flaky composite lithium manganese iron phosphate material.
[0058] Example 2
[0059] The difference from Example 1 is that the molten salt medium is replaced with LiOH and LiNO3, the melting points of LiOH and LiNO3 are measured to be 471.0°C and 250.7°C respectively, the lowest eutectic point is 175.7°C, the composition is x(LiNO3)=62mol%, and finally a flaky composite lithium iron manganese phosphate material is obtained.
[0060] Example 3
[0061] The difference from Example 1 is that glucose is used as a carbon source, and finally a sheet-like composite lithium manganese iron phosphate material is obtained.
[0062] Example 4
[0063] The difference from Example 1 is that glucose and polyvinyl alcohol 17-88 are weighed as carbon sources in a mass ratio of 7:3, and finally a sheet-like composite lithium manganese iron phosphate material is obtained.
[0064] Example 5
[0065] The difference from Example 1 is that glucose and polyvinyl alcohol 17-88 are weighed in a mass ratio of 9:1 as carbon sources, and finally a sheet-like composite lithium manganese iron phosphate material is obtained.
[0066] Example 6
[0067] The difference from Example 1 is that the solid content of the slurry after grinding is 50%, and finally a sheet-like composite manganese iron lithium phosphate material is obtained.
[0068] Example 7
[0069] The difference from Example 1 is that the mass of the black material remains unchanged, the mass ratio of the black material to the molten salt medium is 1:5, and finally a sheet-like composite manganese iron phosphate lithium material is obtained.
[0070] Example 8
[0071] The difference from Example 1 is that the mass of the black material remains unchanged, the mass ratio of the black material to the molten salt medium is 1:2, and finally a sheet-like composite lithium manganese iron phosphate material is obtained.
[0072] Example 9
[0073] The difference from Example 1 is that the activated mixture is transferred to a box furnace and heated to 600° C. for secondary growth under molten salt conditions, and finally a sheet-like composite lithium manganese iron phosphate material is obtained.
[0074] Example 10
[0075] The difference from Example 1 is that the activated mixture is transferred to a box-type furnace and heated to 700° C. for secondary growth under molten salt conditions, and finally a sheet-like composite manganese iron phosphate lithium material is obtained.
[0076] Embodiment 11
[0077] The difference from Example 1 is that the rotation speed of the high-energy ball mill is 800 rpm, and finally a sheet-like composite manganese iron lithium phosphate material is obtained.
[0078] Comparative Example 1
[0079] The difference from Example 1 is that nano-lithium manganese iron phosphate sold on the market is directly used.
[0080] Comparative Example 2
[0081] The difference from Example 1 is that no molten salt medium is added, and finally a flaky composite lithium manganese iron phosphate material is obtained.
[0082] Comparative Example 3
[0083] The difference from Example 1 is that high-energy ball milling to activate the mixture is not performed, and finally a sheet-like composite manganese iron lithium phosphate material is obtained.
[0084] Comparative Example 4
[0085] The difference from Example 1 is that no Mg source, Nb source and V source are added, and finally a sheet-like composite lithium manganese iron phosphate material is obtained.
[0086] Comparative Example 5
[0087] The difference from Example 1 is that only Mg source and Nb source are added to finally obtain a sheet-like composite lithium manganese iron phosphate material.
[0088] Performance Testing
[0089] Test method for lattice constant of sheet composite lithium manganese iron phosphate material: obtained by XRD Rietveld refinement;
[0090] Test method for the diameter and thickness of sheet composite lithium manganese iron phosphate material: Statistical analysis of particle size and thickness is performed using Nano Measurer;
[0091] Test method for the mass content of Mg, Nb and V in flaky composite lithium manganese iron phosphate material: doping elements are analyzed by ICP-OES;
[0092] Test method for the coated carbon content in flaky composite lithium manganese iron phosphate material: Accurately weigh 0.2000g (accurate to 0.0001g) of sample in a ceramic crucible, read the weight on an analytical balance, add about 1.8g of tungsten flux, place it on the instrument crucible support, and conduct oxygen combustion test with a carbon-sulfur analyzer.
[0093] The lattice parameters, tap density, mass content of Mg element, mass content of Nb element and mass content of V element of the sheet-like composite lithium manganese iron phosphate material obtained in the above examples and comparative examples are listed in Table 1.
[0094] Table 1
[0095]
[0096]
[0097] The flaky composite lithium iron manganese phosphate materials of the above embodiment and the comparative example are taken respectively, and the flaky composite lithium iron manganese phosphate material, conductive carbon black (Super P), and binder (polyvinylidene fluoride) are mixed evenly in a mass ratio of 80:15:5, ground sufficiently, and N-methylpyrrolidone is added, and then placed in a vacuum ball mill for ball milling at a speed of 600r / min for 2h; then the positive electrode slurry prepared above is coated on the surface of the aluminum foil current collector by a coating machine, and then baked and cured at 110°C to form a positive electrode active material layer, and then cold pressed to the corresponding thickness by a roller press to obtain a positive electrode sheet.
[0098] The above positive electrode sheet and Li sheet were used as the positive electrode and negative electrode of the lithium-ion battery respectively, Celgard 2400 was used as the separator, and a 1 mol / L LiPF6 mixed solution of EC and EMC (v / v=1:1) was used as the electrolyte solution. The button cells were assembled and tested. The specific test results are shown in Table 2.
[0099] Table 2
[0100]
[0101]
[0102] Combining the contents of Table 1 and Table 2, the following conclusions can be verified:
[0103] By comparing Examples 1, 3, 4 and 5, it is proved that the necessity of using a composite carbon source in this embodiment is that a single carbon source is prone to uneven carbon distribution during the sintering process due to the difference in melting and boiling points. The use of a composite carbon source makes it easier for the coated carbon to form a reasonable dispersion and contact surface on the surface of the lithium manganese iron phosphate material, thereby effectively improving the performance of the material.
[0104] By comparing Examples 1, 7 and 8, it can be seen that reducing the molten salt medium that provides liquid phase conditions will cause the particles to lack sufficient liquid phase conditions, resulting in insufficient secondary growth of particles during the synthesis process. Although reducing the molten salt medium in Example 8 will not lead to a decrease in the electrical properties of its flaky composite lithium manganese iron phosphate material, it will result in higher costs.
[0105] By comparing Examples 1, 9, 10 and 11, it can be seen that the temperature in the molten salt melting process and the synthesis temperature of the material need to be reasonably designed. If the molten salt melting temperature is too high, the molten salt components will volatilize, and if the material synthesis temperature is too high, the particles will grow excessively. That is, although the volatilized molten salt in Example 10 will not cause the electrical properties of the flaky composite lithium manganese iron phosphate material to decrease, it will cause certain environmental pollution and increase in energy consumption.
[0106] Since high-energy ball milling was not used for activation in Comparative Example 3, the particles were not dense due to the lack of high-energy extrusion and collision, and thus the tap density was not improved.
[0107] The poor electrical performance of the sheet-like composite lithium iron manganese phosphate materials in Comparative Examples 4 and 5 fully proves that the lithium iron manganese phosphate materials need to be modified by doping.
[0108] Figure 1 The phase diagram of LiOH-LiCl is shown. Figure 1 It can be seen that the melting points of LiOH and LiCl are 471°C and 605°C respectively, the lowest eutectic point of LiOH and LiCl is 294.5°C, and the composition is x(LiCl)=37mol%.
[0109] Figure 2 The XRD pattern of the composite lithium iron manganese phosphate electrode material prepared in Example 1 is shown. Figure 2Compared with the standard XRD spectrum of lithium manganese phosphate, it can be determined that Example 1 synthesized a pure phase olivine structure lithium iron manganese phosphate material, no impurity peaks were seen, and the peak shape was relatively narrow, and the peak intensity was high, indicating that the crystallinity of the crystal was relatively good. Therefore, using mixed lithium salt as a molten salt medium did not affect the synthesis of the crystal, thus proving that the use of this molten salt method can be used for the synthesis of electrode materials.
[0110] Figure 3 The SEM image of the composite manganese iron phosphate lithium electrode material prepared in Example 1 is shown. It can be seen that the lithium manganese iron phosphate and the graphite particles are mechanically fused after strong collision and extrusion, causing the particles to aggregate on the zirconium balls. The peeled particles are heated, and under the liquid phase conditions provided by the molten salt, the microscopic particles continue to grow and eventually form thin flakes.
[0111] Figure 4 This is the SEM image of lithium manganese iron phosphate purchased from the market. It can be seen that the primary particles are very small, which makes it difficult to increase the compaction density of the material. It also causes the viscosity of the slurry to be high during the slurry mixing process, making coating difficult.
[0112] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0113] In the sheet-shaped composite lithium manganese iron phosphate material of the present application, by doping Mg, V and Nb into the lithium manganese iron phosphate structure, the advantages of each doped metal ion can be combined to improve the crystal structure, electrical conductivity and cycle performance of the sheet-shaped composite lithium manganese iron phosphate material. 2+ The ionic radius is smaller than that of Mn 2+ After doping, the MO bond length in the MO6 octahedron becomes shorter, and the Li-O bond length in the LiO6 octahedron becomes longer. The extension of the Li-O bond makes the Li + The diffusion channel of Li is wider. + It is easier to migrate, thereby increasing the carrier density of the sheet-like composite lithium manganese iron phosphate material, which is beneficial for the multi-component olivine structure cathode material to have better electrochemical performance. 5+ and Nb 5+ Ion defects are generated, and mixed valence states are favorable for Li + De-embedding inside the material. By changing the crystal structure inside the lithium manganese iron phosphate through ion doping, the original lithium manganese iron phosphate lattice has defects, making Li +The diffusion channel is expanded, and the carrier density of the flaky composite lithium iron manganese phosphate material is increased, which can improve the electrochemical performance of the flaky composite lithium iron manganese phosphate material to a certain extent. Therefore, by doping Mg, V and Nb elements, the lithium iron manganese phosphate nanoparticles are reconstructed into a flaky form through microstructure, and the sheet diameter of the flaky composite lithium iron manganese phosphate material is 0.5μm to 2μm, so that compared with the original morphology of lithium iron manganese phosphate, the powder packing density of the flaky composite lithium iron manganese phosphate material in this application is improved, thereby improving the energy density of the flaky composite lithium iron manganese phosphate material. In addition, the carbon coating layer helps to significantly improve the electrical properties of the flaky composite lithium iron manganese phosphate material, such as energy density, discharge specific capacity, rate performance and cycle stability.
[0114] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A sheet-like composite lithium manganese iron phosphate material, characterized in that: The sheet-shaped composite lithium iron manganese phosphate material comprises a composite lithium iron manganese phosphate core and a carbon coating layer coated on the surface of the composite lithium iron manganese phosphate core, wherein the chemical formula of the composite lithium iron manganese phosphate core is LiFe x Mn y A z PO4, wherein 0.2≤x≤0.4, 0.57≤y≤0.78, x+y+z=1; A is Mg element, V element and Nb element; The sheet diameter of the flaky composite lithium manganese iron phosphate material is 0.5 μm to 2 μm, and the tap density of the flaky composite lithium manganese iron phosphate material is 0.9 g / cc to 1.2 g / cc.
2. The sheet-like composite lithium iron manganese phosphate material according to claim 1, characterized in that: The lattice parameters of the sheet-shaped composite lithium manganese iron phosphate material are:
3. The sheet-like composite lithium manganese iron phosphate material according to claim 1 or 2, characterized in that: The mass content of the Mg element is 2000ppm to 3000ppm, the mass content of the V element is 100ppm to 1000ppm, and the mass content of the Nb element is 1000ppm to 2000ppm.
4. The sheet-like composite lithium manganese iron phosphate material according to any one of claims 1 to 3, characterized in that: The thickness of the flaky composite lithium manganese iron phosphate material is 0.2 μm to 0.5 μm; and / or the mass of the carbon coating layer is 1.5 to 2% of the mass of the flaky composite lithium manganese iron phosphate material.
5. A method for preparing the sheet-like composite lithium manganese iron phosphate material according to any one of claims 1 to 4, characterized in that: The preparation method comprises: Step S1, mixing raw materials including a lithium source, an iron source, a manganese source, a phosphorus source, a carbon source, and a doping source and grinding them to obtain a ground slurry; Step S2, spraying the ground slurry to obtain yellow material, and sintering the yellow material in a protective atmosphere to obtain black material; Step S3, subjecting the raw materials including the black material, the molten salt medium and the conductive additive to high-energy ball milling activation to obtain an activated mixture; Step S4, melting, filtering, washing and drying the activated mixture in sequence to obtain the flaky composite lithium manganese iron phosphate material; Wherein, the doping source includes a Mg source, a V source and a Nb source.
6. The preparation method according to claim 5, characterized in that: In the step S1, the carbon source includes glucose, preferably the carbon source is a mixture of glucose and polyvinyl alcohol, preferably the mass ratio of the glucose to the polyvinyl alcohol is (7-9): (3-1), and preferably the polyvinyl alcohol is 88 series polyvinyl alcohol; and / or the Mg source is selected from any one or more of magnesium oxide, magnesium carbonate, magnesium acetate, magnesium lactate, magnesium dihydride and magnesium hydroxide; and / or the V source is selected from any one or more of vanadium pentoxide, ammonium metavanadate, vanadium carbide and vanadyl oxalate; and / or the Nb source is niobium pentoxide and / or niobium oxalate; and / or the lithium source is selected from any one or more of lithium carbonate, lithium hydroxide, lithium acetate and lithium oxalate; and / or the iron source is selected from any one or more of ferric phosphate, ferric oxide, ferric oxide, ferric hydroxide, ferric lactate and ferrous oxalate; and / or the manganese source is selected from any one or more of manganese tetraoxide, manganese carbonate, manganese dioxide and manganese trioxide; And / or the phosphorus source is selected from any one or more of phosphoric acid, ferric phosphate, ammonium phosphate, diammonium hydrogen phosphate and ammonium dihydrogen phosphate.
7. The preparation method according to claim 5 or 6, characterized in that: In step S1, the raw material also includes a solvent, preferably the solvent is selected from any one or more of water, ethanol, methanol and glycerol, and / or the solid content of the slurry after grinding is 30% to 50%, and / or the sand grinding particle size D50 during the grinding process is controlled to be 0.3μm to 0.4μm.
8. The preparation method according to any one of claims 5 to 7, characterized in that: In the step S2, the protective atmosphere is a nitrogen atmosphere; and / or the sintering temperature is 700° C. to 750° C., and the sintering time is 6 h to 10 h.
9. The preparation method according to any one of claims 5 to 8, characterized in that: In step S3, the rotation speed of the high energy ball mill is 400 rpm to 800 rpm; the time of the high energy ball mill is 3 h to 8 h; The mass ratio of the black material to the molten salt medium is 1:(3-5), and / or the melting temperature of the molten salt medium is lower than 600°C, preferably the melting temperature of the molten salt medium is 170°C-600°C, and preferably the molten salt medium is selected from at least two of LiCl, Li2SO4, LiClO4, LiBO2, LiAc, LiNO3, LiOH, Li2CO3 and LiBr; And / or the conductive additive is a flake conductive agent, preferably the flake conductive agent is selected from any one or more of flake graphite, graphene and flake MXene.
10. The preparation method according to any one of claims 5 to 9, characterized in that: In the step S4, the temperature during the melting process is 400° C. to 600° C., and the insulation time is 5 h to 10 h.
Citation Information
Patent Citations
Modified lithium iron manganese phosphate material, preparation method thereof and battery
CN115709976A
Doped lithium iron manganese phosphate positive electrode material, preparation method thereof, positive electrode plate containing doped lithium iron manganese phosphate positive electrode material, and lithium ion battery containing doped lithium iron manganese phosphate positive electrode material
CN116741987A
Lithium ion battery
CN117497828A
Precursor and preparation method thereof, positive electrode material, positive electrode plate and lithium ion battery
CN117509594A
Modified lithium manganese iron phosphate material as well as preparation method and application thereof
CN118099379A
Cited By
Preparation method of superfine lithium manganese iron phosphate nanoparticles embedded in three-dimensional porous carbon skeleton
CN120136062A